Розгортання загальної адаптаційної реакції під впливом води Нафтуся як механізм гальмування росту карциноми герена у щурів - Івасівка, С.В.; Ковбаснюк, М.М. (Медична гідрологія та реабілітація, 2009)
Органические вещества-ксенобиотики воды Нафтуся, запуская развертывание общей адаптационной реакции организма, обеспечивают согласование структурных и функциональных изменений, что позволяет организму эффективно препятствовать опухолевому росту. The organic substances-xenobiotics of the water Naftussya, starting the expansion of the organism’ general adaptative reaction, provide the coordination of structural and functional changes, that allows to the organism effectively to interfere with tumour growth.